Cold extremities in migraine: a marker for vascular dysfunction in women. (20th May 2020) - Linstra, K. M.; Perenboom, M. J. L.; van Zwet, E. W.; van Welie, F. C.; Fronczek, R.; Tannemaat, M. R.; Wermer, M. J. H.; Maassenvandenbrink, A.; Terwindt, G. M.
Abstract : Background and purpose: Migraine is recognized as a vascular risk factor, especially in women. Presumably, migraine, stroke and cardiovascular events share pathophysiological mechanisms. Self‐reported cold extremities were investigated as a marker for vascular dysfunction in migraine. Secondly, it was hypothesized that suffering from cold extremities affects sleep quality, possibly exacerbating migraine attack frequency. Methods: In this case–control study, a random sample of 1084 migraine patients and 348 controls (aged 22–65 years) from the LUMINA migraine cohort were asked to complete questionnaires concerning cold extremities, sleep quality and migraine. Results: A total of 594 migraine patients and 199 controls completed the questionnaires. In women, thermal discomfort and cold extremities (TDCE) were more often reported by migraineurs versus controls (odds ratio 2.3, 95% confidence interval 1.4–3.7; P < 0.001), but not significantly so in men (odds ratio 2.5, 95% confidence interval 0.9–6.9; P = 0.09). There was no difference in TDCE comparing migraine with or without aura. Female migraineurs who reported TDCE had higher attack frequencies compared to female migraineurs without TDCE (4 vs. 3 attacks per month; P = 0.003). The association between TDCE and attack frequency was mediated by the presence of difficulty initiating sleep ( P = 0.02). Conclusion: Women with migraine more often reported cold extremities compared with controls, possibly indicating a sex‐specific vascular vulnerability. Female migraineurs with cold extremities had higher attack frequencies, partly resulting from sleep disturbances. Future studies need to demonstrate whether cold extremities in female migraineurs are a predictor for cardiovascular and cerebrovascular events.